2014
DOI: 10.1016/j.jelekin.2014.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mental fatigue on induced tremor in human knee extensors

Abstract: Northumbria University has developed Northumbria Research Link (NRL) to enable users to access the University's research output. Copyright © and moral rights for items on NRL are retained by the individual author(s) and/or other copyright owners. Single copies of full items can be reproduced, displayed or performed, and given to third parties in any format or medium for personal research or study, educational, or not-for-profit purposes without prior permission or charge, provided the authors, title and full b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 32 publications
3
39
1
3
Order By: Relevance
“…In two studies [10,21] the greater subjective fatigue was also associated with a decline of accuracy. An increase in reaction time over time was observed by Budini et al [34]. In the study of Brownsberger et al [12] the increase in mental fatigue was associated with an increase in -band activity of the prefrontal lobe.…”
Section: Mental Fatigue Inducing Interventionsmentioning
confidence: 79%
See 4 more Smart Citations
“…In two studies [10,21] the greater subjective fatigue was also associated with a decline of accuracy. An increase in reaction time over time was observed by Budini et al [34]. In the study of Brownsberger et al [12] the increase in mental fatigue was associated with an increase in -band activity of the prefrontal lobe.…”
Section: Mental Fatigue Inducing Interventionsmentioning
confidence: 79%
“…peak torque, mean torque, time to half peak torque, time to peak torque and peak torque slope). Budini et al [34] on the contrary reported a decreased leg extension MVC (796 ± 150 N to 741 ± 137 N) after a 100-min mentally fatiguing task. Martin et al…”
Section: Behavioralmentioning
confidence: 90%
See 3 more Smart Citations